PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN KETERAMPILAN MENGGAMBAR DEKORATIF PADA SISWA KELAS III SDN 21 PEKANBARU - Marita, Seri Marita Seri; Antosa, Zariul Antosa Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:The background of this research is the lack of drawing skillsdecorative third grade students of SD Negeri 21 Pekanbaru, of the 30 students who areskilled in decorative drawing only 14 students (46.7%), while students who are notskilled in decorative drawing as many as 16 students (53.3% ). This study is aClassroom Action Research (CAR) conducted aims to improve the skills of drawingdecorative Elementary School third grade students 21 Pekanbaru with immediateapplication of learning models. Formulation of the problem: Is Pembelaran DirectApplication Model can improve drawing skills decorative in Class III SD Negeri 21Pekanbaru ?. Penilitian subject is third grade students of SD Negeri 21 Pekanbaru witha total of 30 people consisting of 17 male students and 13 female students. Datacollection instruments in this thesis is the teacher and student activity sheets and theresults of the students skills. Results of research and discussion in mind that theapplication of direct learning model can improve drawing skills decorative ElementarySchool third grade students 21 Pekanbaru. It is known from prior learning skills ofstudents with direct instruction only be achieved at an average of 68.1. In the first cycleor after the implementation of direct learning model, the average skills of studentsincreased to 56.7%, then increased to 72.1 in the second cycle. The classical skillsachieved in 30 students (100% of students skilled). Thus, it can be concluded that theapplication of direct learning model can improve drawing skills dekroratif secondgrade students of SDN 21 Pekanbaru.Keywords: Model Learning and Skills Jump Decorative Drawing.